Mastery of information technology and self-efficacy in enhancing technopreneurship readiness among vocational school student - Ni Ketut Kertiasih; Djoko Kustono; Purnomo; Eddy Sutadji (Association for Scientific Computing Electrical and Engineering, 2024)
This study aims to analyze the contribution of information technology mastery and self-efficacy in fostering technopreneurship readiness among vocational students. Technopreneurship is a business field that utilizes information technology and presents a viable solution to unemployment. Meanwhile, vocational school graduates have a significant opportunity to pursue technopreneurship. To support these graduates’ readiness in the field of technopreneurship, it is necessary to equip them with information technology and self-efficacy skills. With these skills, vocational school graduates have the opportunity to become independent workers and create new jobs based in the field of information technology.The rapid development of information and communication technology high lights the importance of students’ mastery of this field. These skill sarenecessary for students to compete, beresponsible, and exhibit creativity and innovation. Additionally, self-efficacy refers to anindividual’s belief and confidence in their ability to influence their environment. It is a crucial factor in determining students’ readiness to work. By enhancing their self-efficacy, students can be motivated to establish new businesses based on information technology. There fore, this research employed a correlational quantitative method, focusing on vocational students in Buleleng Regency, with a sample size of 167. Regression analysis was used to analyze the data with two predictors. The finding sindicated that the mastery of information technology and self-efficacy significantly contributed to the technopreneurship readiness of vocational students. Keywords: mastery of information technology, self-efficacy, technopreneurship readiness